2013
DOI: 10.3109/0886022x.2013.815546
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of rutin on hexachlorobutadiene-induced nephrotoxicity

Abstract: Hexachlorobutadiene (HCBD) is a potent nephrotoxin which nowadays contaminates human foods and water. On the other hands, it has been reported that rutin is a chemopreventive flavonoid which exerts some protective effects on the kidney. Therefore, in this work, the possible effect of rutin on HCBD-induced nephrotoxicity was investigated in female rats. The animals were divided into five groups. Groups 1 and 2 were treated with vehicle and HCBD (100 mg/kg, i.p.), respectively. Groups 3-5 were pretreated with ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 39 publications
1
22
0
Order By: Relevance
“…Also emodin which is found in rheum genus has nephroprotective effects against metals by inhibition of proliferation of renal mesangial cells (MSCs) and thus lower cellular DNA [25]. In addition, rutin as an active ingredient in rheum genus [26] showed nephroprotective effect against cisplatin [27] and hexachlorobutadien [6]. Isolated anthraquinones from rheum genus revealed protective effects against mercuric chloride in rats [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also emodin which is found in rheum genus has nephroprotective effects against metals by inhibition of proliferation of renal mesangial cells (MSCs) and thus lower cellular DNA [25]. In addition, rutin as an active ingredient in rheum genus [26] showed nephroprotective effect against cisplatin [27] and hexachlorobutadien [6]. Isolated anthraquinones from rheum genus revealed protective effects against mercuric chloride in rats [28].…”
Section: Discussionmentioning
confidence: 99%
“…tenuated the nephrotoxicity of HCBD such as safranal [5], rutin [6], pomegranate seed oil [7]. Our recent studies have shown Rheum turkestanicum has antidiabetic effect [8] and cardio protective effect against doxorubicin [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Total thiol groups were measured using 2,2′-dinitro-5,5′-dithiodibenzoic acid (DTNB) which reacts with the SH groups to produce a yellow colored complex with peak absorbance at 412 nm [23,24]. In summary, 1 mL Tris-EDTA buffer was added to 50 μL of BALF and sample absorbance was read at 412 nm against Tris-EDTA buffer alone (A1).…”
Section: Methodsmentioning
confidence: 99%
“…There are several flavonoids such as rutin (Sadeghnia et al, 2013), naringin (Sahu et al, 2014), and herbs containing flavonoids such as date fruit (El Arem et al, 2014), Murraya paniculata (Zou et al, 2014) exhibit nephroprotective activity, these flavonoids might undergo glucuronide-sulfate conjugate modification in vivo. Our results showed that the relationship between flavonoid glucuronide-sulfate conjugates and nephroprotective activity need further studied.…”
Section: Discussionmentioning
confidence: 99%